Improving reading skills through effective reading Strategies - Zokirova, Dilsora (European Journal of Life Safety and Stability (2660-9630), 2023)
Researchers have found that teaching reading strategies is a key element in developing student comprehension. However, many teachers lack a solid foundation for teaching these reading comprehension strategies. Therefore, teachers need to be prepared on how to design effective comprehension strategies and how to teach these strategies to their students. Therefore this study aims to study the effective reading strategies in order to improve reading skills in language classes.